Assessment of Antimicrobial and Proteolytic Activity of Lactic Acid Bacteria Isolated from Dadih: Naturally Fermented Buffalo Milk From West Sumatra, Indonesia - Chandra Utami Wirawati; Yatim Rahayu Widodo (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2021)
Dadih is a traditional fermented food from West Sumatra Indonesia and had become an integral diet and culture for Minangkabau tribes. The aims of this study were evaluated antimicrobial and proteolytic activity of lactic acid bacteria (LAB) isolated from dadih. Four different dadih samples was taken from 2 origins based on fermentation methods. Samples were isolated and screening for morphological, genotype and phenotype characteristic. Isolation was conducted in de Man Rogosa Sharpe (MRS) agar containing 0.5% CaCO3 followed by morphological identification. All isolates were selected based on antimicrobial and proteolytic activity with agar well diffusion method. Finally, the selected isolate were identified based on 16S rRNA partial gene sequence analysis and fermentation profile using API 50 CHL kit test. Seventeen isolates not only exhibited wide spectrum of antimicrobial activity against gram positive and negative bacteria, but also high proteolytic activity. Partial gene sequence analysis and API 50 CHL kit showed 12 isolates were identified as Lactococcus lactis, 3 isolates were identified as Lactobacillus plantarum, and 1 isolate each was identified as Lactobacillus pentosus and Pediococcus pentosaceus respectivelly. The result shows that dadih was a potential source of LAB with high antimicrobial (range between 1.0 to 6.1 mm) and proteolytic traits (range between 15 to 2.1 mm). This makes it possible to develop the functional properties of these isolates as a starter culture in milk fermentation.